First records of Mops johorensis (Dobson, 1873), Northern Free-tailed Bat (Chiroptera, Molossidae), from Borneo, with new information on their genetics and echolocation calls - Faisal Ali, Anwarali Khan; Muhd Amsyari, Morni; Julius William, Dee; Jayaraj Vijaya, Kumaran; Emy Ritta, Jinggong; Praveena, Rajasegaran; Qhairil Shyamri, Rosli; Norfarhana, Mazlan; Wan Nursyafinaz, Wan Azman; Siti Nurbaidzuri, Reli @ Raily; Ummu Safiyyah, Daud; Amirrah, Amat; et al. (Pensoft Publishers, 2025)
This study presents the first confirmed records of Mops johorensis (Dobson, 1873) (Chiroptera, Molossidae) from Borneo. Specimens were recorded at three sites: Sabah (Sungai Kangkawat, 50 m a.s.l) and Sarawak (Lubok Antu, 30 m a.s.l and Mount Penrissen, 1200 m a.s.l). Echolocation analysis revealed site-based variation in call frequencies. Morphological comparisons showed subtle differences between Bornean and Peninsular populations. Genetic analysis using the mitochondrial COI gene showed minimal divergence between Bornean and Peninsular individuals. Spatial modelling identified hotspots for Molos-sidae in northern Sabah and central Sarawak, with habitat suitability strongly influenced by bat and cave density, climate, and land use.